Doing research in sport and exercise a student's guide - Smith, Mark F. (SAGE, 2022)
Split into five sections that cover your whole research journey, this book captures everything you need to understand to do a sports research project. From getting started with a research question and selecting a research approach to choosing a method of data collection and analysing and presenting research findings, it walks you step-by-step through the entire research process. The book also: Showcases a diverse range of approaches, including experiments, surveys, focus groups, interviews, systematic reviews and mixed methods, to help you choose the best option for your project. Focuses on applied research, showing you how to go beyond the classroom, conduct research in the field and manage and analyse data in the real world. Explores how your supervisor can support you to get the most out of your project. Features include over 40 student activities that encourage you to think more deeply about what you've learned, nearly 50 case studies highlighting research from real-world students and sport researchers, and reflection points, to help you check your understanding. For students across courses relating to Sport & Exercise Science, Coaching Practice & Development, PE and Sport, this book is a down-to-earth guide to help anyone doing a research project in sport and exercise.